Graphdiyne Visible‐Light Photodetector with Ultrafast Detectivity. Issue 6 (12th January 2021) - Li, Yuan; Zhang, Mingjia; Hu, Xiuli; Li, Xiaodong; Li, Ru; Yu, Lingmin; Fan, Xinhui; Wang, Naiyin; Huang, Changshui; Li, Yuliang
Abstract: Two‐dimensional (2D) materials have captured a tremendous amount of attention worldwide due to their unique physical and chemical properties. Herein, a mesoscopic graphdiyne (GDY) film is prepared through a facile solution method and directly used to construct an ultra‐fast visible light detector. This GDY thin film‐based photodetector exhibits both stable and repeatable high‐performance photoelectric responses to the visible light with various wavelengths. Among the visible light range, the GDY thin film is discovered to be most sensitive to 640 nm laser, which can enable it to achieve the highest response value of up to 46300%, thus conferring GDY materials an undeniable superiority of application in photoelectric devices. Especially, such GDY‐based detectors demonstrate ultra‐fast response speeds with an ephemeral response/recovery time of only 5.15/19.83 µs, which is far better than most reported photosensitive materials, including inorganic materials, low‐dimensional composites, and heterojunctions. This study suggests that GDY thin films can be regarded as new promising candidates for application as rapid photoelectric sensors. More importantly, this paper reveals the vast potential of such sp‐hybridized carbon as novel carbon‐based semiconductors in future optoelectronic applications due to their unique structure and energy band. Abstract : Solution‐synthesized graphdiyne thin films are utilized to readily assemble visible light detectors. Benefiting from the rapid charge transfer, the graphdiyne‐based photodetectors produce a high sensitivity and demonstrate an ultra‐fast response. These results verify the advantages of the application of graphdiyne semiconductors in photodetectors/sensors, promoting the development of high‐precision optoelectronic devices.